EU and OECD Benchmarking and Peer Review Compared - Groenendijk, Nico S. (The EU and Federalism, 2011)
Benchmarking and peer review are essential elements of the EU's open method of coordination (OMC) and are applied in order to stimulate mutual learning processes, to perform multilateral surveillance and to contribute to further convergence of member states' policies in various policy fields. However, the current use of benchmarking within the OMC suffers from two main flaws (Groenendijk 2008). First, OMC benchmarking approaches and practices are generally poorly designed and overlook the fact that different purposes and contexts call for different types of benchmarking; more generally, different coordination issues need different procedures (Heise 2008). Secondly, in some areas (especially in social policies) benchmarking may not be a sufficient coordination tool, and it is at best additional to coordination by means of enforceable sanctions.